2011
DOI: 10.1021/nn2033105
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Intracellular Release of Doxorubicin in Multidrug-Resistant Cancer Cells by Tuning the Shell-Pore Sizes of Mesoporous Silica Nanoparticles

Abstract: In this work, hollow mesoporous silica nanoparticles (HMSNs) with three pore sizes were manufactured to control the drug release rate, and the biological roles of these HMSNs were evaluated in multidrug-resistant (MDR) cancer cells. As novel pore-size-controllable inorganic materials, HMSNs showed negligible cytotoxicity and efficient cellular uptake toward drug-sensitive MCF-7 and drug-resistant MCF-7/ADR cells. Doxorubicin (DOX)-loaded HMSNs (DMSNs) not only demonstrated effective drug loading and a pH-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
234
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 368 publications
(239 citation statements)
references
References 39 publications
3
234
1
1
Order By: Relevance
“…Very recently, several studies have demonstrated that SN particles not only can serve as promising drug carriers for high tumor targeting efficiency and therapy efficacy, but also for reducing the systematic toxicity [16,17]. However, the biological safety effect is sill being a pendent question of SN particles [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, several studies have demonstrated that SN particles not only can serve as promising drug carriers for high tumor targeting efficiency and therapy efficacy, but also for reducing the systematic toxicity [16,17]. However, the biological safety effect is sill being a pendent question of SN particles [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…108 Gao et al used different sizes of MSNs to carry DOX, and then used them against drug-resistant breast cancer cells (MCF-7/Adr); the results suggested that the antitumor activity of MSNs showed a dependence on the pore size. 109 The larger pore size of MSNs can make the cancer cells to absorb DOX faster, so that the rapid accumulation of intracellular drugs plays a strong role in the reversal of MDR. It is clear that MSNs as a carrier for targeted therapy have great potential for overcoming MDR.…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 99%
“…Also, at pH 5.5 faster DOX release was observed for both particles compared to that at pH 7.4, which is in good accordance with the previous reports. 22 The slow rate of DOX release from F127-OMSN can provide more effective therapy by preserving desired drug concentration in the body for longer times.…”
mentioning
confidence: 99%